?SYNTHESIS AND CHEMICAL REACTIVITY OF NOVEL FUNCTIONALLY SUBSTITUTED- 5,6-DIPHENYL-l,2,4-TRIAZINES - Morsy, J M; Ismail, F; Rahman, R M Abdel-; Amine, H A (Biological Sciences - PJSIR, 2000)
An improved synthesis of some newfully substituted-5,6-diphenyl-l,2,4-triazines starting from 4H-2-cyanomethyl/aryl-5,6- diphenyl-l,3,4-oxadiazines (3a-d) has been reported. The structures were determined through elemental analysis and spectral data.The mass spectraof thesynthesizedcompounds werealso studied.Someof thesecompoundsexhibited significant antimi- crobial activity.